Attitudes and principles of making. Issue 1 (1st April 2016) - Ellis, Simon
This is a list of principles – or perhaps attitudes – of choreographic practice and making. The list is not exhaustive, and indeed comprises many ideas that are so general that they would hold for any kind of making. In such a way they demand that we consider to what extent choreographic making is special at all. Perhaps the list might – as we continue to consider the nature of choreographic practices – help to provoke our questions, our processes, our methods and our choreographies.